PENGARUH LITERASI KEUANGAN, LIFE STYLE HEDONIS, DAN FINANCIAL TECHNOLOGI TERHADAP PERILAKU KEUANGAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI PADA MAHASISWA PERGURUAN TINGGI SWASTA DI KOTA SURAKARTA - Iga Novitasari; Nur Endah Fajar Hidayah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of financial literacy, hedonic lifestyle, and financial technology on the financial behavior of students in private universities in Surakarta, with locus of control as a moderating variable using a quantitative approach. The data used include primary data obtained through. The population in this study were private university students in Surakarta, with a total of 25,250 students. The sample used in the study was determined as many as 200 respondents using the random sampling method. The data analysis technique used multiple linear regression and MRA to test the relationship between variables and the role of locus of control moderation processed through the SPSS 25 program. The results of the study showed that financial literacy and financial technology have a positive and significant influence on financial behavior. While hedonic lifestyle has a negative and significant influence on financial behavior. Locus of control is proven to moderate the relationship between financial literacy, financial technology on financial behavior, but does not moderate the relationship between hedonic lifestyle on financial behavior. These findings provide important insights for the development of financial education programs in higher education, by considering psychological factors such as locus of control in designing effective interventions to improve students' financial behavior.